Effect of supplementing epinephrine in maturation media on the developmental competence of buffalo oocytes - Ali Husnain; Abdul Khaliq; Talha Ashraf; Abdul Rehman; Muhammad Yasir Zahoor; Muhammad Binyameen; Amjad Riaz (Revista Científica)
Epinephrine is a catecholamine that plays a vital role during cellular stress by scavenging free radicals. During in vitro maturation, oocytes experience stressful conditions that likely compromise their development. The objective of the experiment was to investigate the effect of the addition of epinephrine in IVM media on nuclear maturation and in vitro developmental competence of oocytes. Buffalo oocytes were harvested from slaughterhouse ovaries. Oocytes of A and B grade were matured for 24 hours in IVM media supplemented with increasing concentrations of epinephrine 0, 0.01, 1.0, and 100 μM. The maturation of oocytes was examined based on the nuclear maturation after staining with Hoechst 33342 (Sigma Aldrich, St. Louis, MO, USA). After maturing with epinephrine, oocytes were fertilized for 6 hours with post-thawed semen from a single bull. Presumptive zygotes were cultured in commercial media (IVF Bioscience, Falmouth, UK), and cleavage was observed 48 hours after fertilization. The blastocyst rate was assessed on day 7 of the culture. Maturation and fertilization media were prepared in-house. Blastomere was counted from the hatched blastocyst after staining with Hoechst 33342 using an inverted microscope equipped with Cellsens software. The data was analyzed using the GLIMMIX procedures of SAS. The statistical model included the fixed effect of treatment and random replication. Orthogonal polynomial contrasts were built to assess the dose-response of epinephrine. Results represented as least square means and respective standard error of means (LSM ± SEM). Adding epinephrine to the maturation media did not affect the nuclear maturation and cleavage. Media supplemented with epinephrine at 0, 0.01, 1.0, and 100 μM concentrations had a proportion of meiotic I and II oocytes of 83.1 ± 6.0, 85.5 ± 6.3, 75.3 ± 5.9, and 70.9 ± 6.4%) and cleavage rate of 58.2 ± 4.6, 60.5 ± 4.6, 54.7 ± 4.5, and 47.8 ± 4.4%) respectively. However, the proportion of blastocyst out of matured oocytes was increased (p=0.01; 35.9 ± 4.5, 43.2 ± 4.8, 36.0 ± 4.3, and 25.8 ± 3.8%) with epinephrine supplementation and the response was maximized (Quadratic effect; p=0.01) at 0.01 μM concentration. Consistently, the proportion of blastocyst out of cleaved embryos tended to increase (p=0.13; 62.1 ± 5.0, 72.4 ± 4.6, 66.7 ± 4.7, and 55.3 ± 5.3%) with epinephrine and the response was maximized (Quadratic effect; p=0.04) at 0.01 μM concentration. Supplementation of epinephrine in maturation media increased (p<0.01) the blastomere number, and response was maximized (Quadratic effect; p<0.01) at 1.0 μM concentration. It is concluded that supplementing  epinephrine in maturation media had a favorable effect on the blastocyst formation, and significant benefits were observed at 0.01 μM concentration.